Pengembangan Media Pop Up Book untuk Penguasaan Kosakata Siswa Kelas VIII di Madrasah Tsanawiyah Negeri Palopo - Kartini Kartini; Mubassyirah Bakri; Justi Tambing (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research discusses the development of pop-up book media for vocabulary mastery among eighth-grade students at Madrasah Tsanawiyah Negeri Palopo. The aim of this research is (1) to understand the process of developing pop-up book media for vocabulary mastery among eighth-grade students at Madrasah Tsanawiyah Negeri Palopo. (2) to determine the validity level of the pop-up book media for vocabulary mastery among eighth-grade students at Madrasah Tsanawiyah Negeri Palopo. This type of research is development research using the Research and Development (R&D) approach with the ADDIE model. The data collection methods include observation, interviews, questionnaires, and documentation. The results of this study show that the validation score from the media expert is 93.33%, categorized as highly valid. The validation score from the subject matter expert is 95.38%, also categorized as highly valid. The validation score from the learning expert is 80%, categorized as valid. The trial results obtained a percentage of 83.24%, categorized as highly feasible. Therefore, it can be concluded that the pop-up book media is highly feasible for use in teaching Arabic to eighth-grade students.